Szerzői jogi szankciórendszerünk a szellemi tulajdonjogok érvényesítéséről szóló 2004/48 EK irányelv tükrében - Kiss, Tibor (Debreceni Jogi Műhely, 2005)
Copyright law is a relative young area of civil law. Intellectual property and creations ensure the revelation of human personality. The infringement of these rights became general with the development of technology. From the beginning copyright law tried not only circumscribe the possibilities of unrestricted use but ensure effective protection to authors with exact sanctions.In the essay I examine the international and Hungarian regulation against usurpation demonstrating all sanctions and opportunities. Not only one area of law gives protection to these rights. Civil law, criminal law and administration law has different sanctions for infringements.On 29th April 2004 2004/48/EC directive has been accepted about validation of intellectual property rights. The explanation of this directive is that different regulations in member states endanger the unified internal market. The directive consists of the rules of proceedings and sanctions.In this study I present the development about system of sanctions form an international and from a Hungarian perspective. I examine all types of sanctions concerning to the field of civil law and try to analyze functions and aims in connection with them. The effectiveness and history of these legal institutions are also presented in the study.Comparing the directive and the Hungarian copyright law it can be said that despite of all circumstances the Hungarian law has to be improved especially on the field of proceedings and temporary arrangements. These rules are specified compared to the ones in the Hungarian civil procedure, so judges have to take care of these differences.